Search for correlations of high-energy neutrinos and ultrahigh- energy cosmic rays - Schumacher Lisa (EPJ Web of Conferences, 2019)
The IceCube Neutrino Observatory has recently found compelling evidence for a particular blazar producing high-energy neutrinos and PeV cosmic rays, however the sources of cosmic rays above several EeV remain unidentified. It is believed that the same environments that accelerate ultra-high-energy cosmic rays (UHECRs) also produce high-energy neutrinos via hadronic interactions of lower-energy cosmic rays. Two out of three joint analyses of the Ice- Cube Neutrino Observatory, the Pierre Auger Observatory and the Telescope Array yielded hints for a possible directional correlation of high-energy neutrinos and UHECRs. These hints however became less significant with more data. Recently, an improved analysis with an approach complementary to the other analyses has been developed. This analysis searches for neutrino point sources in the vicinity of UHECRs with search windows estimated from deflections by galactic magnetic fields. We present this new analysis method for searching common hadronic sources, additionally including neutrino data measured by ANTARES in order to increase the sensitivity to possible correlations in the Southern Hemisphere.